(untitled) (Asian Journal of Ethnobiology, 2020)
Abstract. Babalola OJ, Jegede HO, Ogundro BN. 2020. Perceptions, attitudes, and outcomes of human-snake encounters: A retrospective study of an online discussion community in Nigeria. Asian J Ethnobiol 3: 1-9. The internet is a valuable tool for obtaining data needed to study factors that hinder snake conservation, especially in resource-limited settings. There is a lack of peer-reviewed research on the use of online communities to examine factors contributing to undesirable human-snake conflicts in Nigeria. A 12-month dataset (August 2016-July 2017) on human-snake encounters shared on Nairaland®- a popular online community forum in Nigeria - was retrieved and analyzed. Morphological characteristics observed in the snake photographs posted on the platform were used for species identification. A total of 203 human-snake encounters were recorded from 32/37 States of Nigeria. Men (n=133) reported more human-snake encounters than women (n =11), while ‘reporters’ of unspecified gender (n =59) accounted for the rest. Most postings were from the southern part of Nigeria, with the highest number of postings from Lagos State (n =34). Of the 24 snake species reported in the study, the African Rock Python was the most encountered. The months of May to July recorded the highest number of snake species reported by the respondents. ‘Fear’ and ‘food’ were the significant perceptions elicited by people during snake encounters. Human-snake conflicts resulted in snake deaths (n =182) irrespective of snake venomosity. Only 1.0% (n=2) of the snakes were protected from harm. This study revealed that data from online community forums are helpful for retrospective analyses of the perceptions and outcomes of human-snake encounters, the output of which policymakers and conservationists may find helpful.